Evaluating the effect of recombinant human growth hormone treatment on sleep-related breathing disorders in toddlers with Prader-Willi syndrome: a one-year retrospective cohort study - Haiyan Guo; Jinrong Fu; Yufeng Zhou; Feihong Luo; Ruoqian Cheng (BMC, 2024)
Abstract Background Recombinant human growth hormone (rhGH) therapy is beneficial for children with Prader-Willi syndrome (PWS) in improving short stature and metabolism, but the effect of early rhGH treatment on respiratory and sleep parameters for PWS children under three years old remains elusive. Thus, this study aimed to investigate the impact of rhGH treatment on sleep-related breathing disorders (SRBDs) for toddlers with PWS. Methods A total of 17 age-matched PWS patients receiving rhGH treatment (rhGH group) and 17 control individuals not receiving rhGH treatment (non-rhGH group) were recruited for this study between October 2018 and January 2023. Data related to polysomnography-polygraphy (PSG) and serum levels of insulin-like growth factor (IGF-1) and insulin-like growth factor binding protein 3 (IGFBP-3) were collected. Results The mean age in the rhGH group was 20.76 ± 9.22 months, which was comparable to that of the non-rhGH group (25.23 ± 13.81 months). The demographic and anthropometric parameters were similar across the two groups after 52 weeks of treatment. Administration of rhGH to toddlers did not exert adverse effects on the obstructive apnea-hypopnea index (OAHI), central apnea index (CAI), oxygen desaturation index (ODI), mean percutaneous oxygen saturation (SpO2), lowest SpO2, duration when SpO2 is lower than 90%, or proportion of the patients with SpO2 lower than 90%. Furthermore, the increased IGF-1 z-score and IGFBP-3 level did not worsen SRBDs. Conclusion Treatment with rhGH for 52 weeks on young toddlers with PWS showed no deleterious effects on SRBDs. This shed more light on the importance of initiating rhGH therapy early in PWS patients.